MENGUNGKAP PEMAHAMAN PERAN AKUNTAN PENDIDIK: STUDI FENOMENOLOGI - Wiwik Mukholafatul Farida (Jurnal Reviu Akuntansi dan Keuangan)
This article aims to understand the accountant educator about their roles in accounting learning. This research is qualitative with phenomenology approach, under the interpretive paradigmas the umbrella. Phenomenology by Edmund Husserl is referred to as data analysis by selecting3 accounting educator as research informants. Based on the investigation, it was found thatthere are four roles of educator revealed by the informants, among others: (1) setting plot oflearning (mudarris); (2) accompanying college student in the learning (rafiqu ta’lim); (3) showingthe path of the truth (murabbi);Understanding role awareness is inseparable from the experience, assessment, and perspective accounting educator’s.Keyword: Role, Accounting Educator, Phenomenology